Endothelium-derived nitric oxide and vascular physiology and pathology - Arnal, J.-F.; Dinh-Xuan, A.-T.; Pueyo, M.; Darblade, B.; Rami, J. (Cellular and molecular life sciences : CMLS, 1999)
In 1980, Furchgott and Zawadzki demonstrated that the relaxation of vascular smooth muscle cells in response to acetylcholine is dependent on the anatomical integrity of the endothelium. Endothelium-derived relaxing factor was identified 7 years later as the free radical gas nitric oxide (NO). In endothelium, the amino acid L-arginine is converted to L-citrulline and NO by one of the three NO synthases, the endothelial isoform (eNOS). Shear stress and cell proliferation appear to be, quantitatively, the two major regulatory factors of eNOS gene expression. However, eNOS seems to be mainly regulated by modulation of its activity. Stimulation of specific receptors to various agonists (e.g., bradykinin, serotonin, adenosine, ADP/ATP, histamine, thrombin) increases eNOS enzymatic activity at least in part through an increase in intracellular free Ca2+. However, the mechanical stimulus shear stress appears again to be the major stimulus of eNOS activity, although the precise mechanisms activating the enzyme remain to be elucidated. Phosphorylation and subcellular translocation (from plasmalemmal caveolae to the cytoskeleton or cytosol) are probably involved in these regulations. Although eNOS plays a major vasodilatory role in the control of vasomotion, it has not so far been demonstrated that a defect in endothelial NO production could be responsible for high blood pressure in humans. In contrast, a defect in endothelium-dependent vasodilation is known to be promoted by several risk factors (e.g., smoking, diabetes, hypercholesterolemia) and is also the consequence of atheroma (fatty streak infiltration of the neointima). Several mechanisms probably contribute to this decrease in NO bioavailability. Finally, a defect in NO generation contributes to the pathophysiology of pulmonary hypertension. Elucidation of the mechanisms of eNOS enzyme activity and NO bioavailability will contribute to our understanding the physiology of vasomotion and the pathophysiology of endothelial dysfunction, and could provide insights for new therapies, particularly in hypertension and atherosclerosis.